2020
DOI: 10.3390/diagnostics10121075
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vitamin D Levels, Bone Metabolic Marker Levels, and Bone Mineral Density among Patients with Thyroid Disease: A Cross-Sectional Study

Abstract: Thyroid hormones have a catabolic effect on bone homeostasis. Hence, this study aimed to evaluate serum vitamin D, calcium, and phosphate and bone marker levels and bone mineral density (BMD) among patients with different thyroid diseases. This cross-sectional study included patients with underlying thyroid diseases (n = 64, hyperthyroid; n = 53 euthyroid; n = 18, hypothyroid) and healthy controls (n = 64). BMD was assessed using z-score and left hip and lumbar bone density (g/cm2). The results showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Peculiar to our cases is the fact that recurrent hypocalcemic tetany was the first presentation of these women who were eventually diagnosed with hyperthyroidism. In addition, the recurrence of hypocalcemic tetany ceased after the treatment of hyperthyroidism, which is in keeping with findings of the few studies that reported same [5-7].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Peculiar to our cases is the fact that recurrent hypocalcemic tetany was the first presentation of these women who were eventually diagnosed with hyperthyroidism. In addition, the recurrence of hypocalcemic tetany ceased after the treatment of hyperthyroidism, which is in keeping with findings of the few studies that reported same [5-7].…”
Section: Discussionsupporting
confidence: 88%
“…This is mediated predominantly by thyroid hormone receptor-α [2]. Previous reports from the West also showed that hyperthyroid persons have normal or increased serum total calcium [3-5].…”
Section: Introductionmentioning
confidence: 99%
“…Violation of hormonal regulation complicates the course of chronic generalized periodontitis, and a more severe course is characteristic of patients with hypothyroidism. The lower jaw is more sensitive to changes in thyroid hormone levels [8]. Studies show a decrease in the mineral density of the alveolar process in patients with hypothyroidism, which may be one of the pathogenetic mechanisms of chronic generalized periodontitis in this group of people [9].…”
Section: Introductionmentioning
confidence: 99%